(3GdJNWjW hGdQbGHI GdeGdjI aj GdefTBJ GdRQGYjI (B/s - (3UHQj, fVGd QTjOs ((3YeGf(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 1994)
(3ebOeI aj GdJYQja HGdefTCI GdRQGYjI h GdJYQja HGdfXGe GdeMGSHj ajgG h GSJNOGe GdJNWjW h GdQbGHI GdeGdjI ajgG h JfGhd GdJNWjW HGSJNOGe GdehGRfI GdJTZjdjI h JNWjW GdGSJKeGQGJ WhjdI GdGLd h GdHQeLI GdNWjI aj GdefTGI GdRQGYjI h feGPL CNQi aj GdJNWjW GdeGdj ceG Je GdJWQb Gdi GdQbGHI Ydi COGA GdYed aj GdefTCI GdRQGYjI h GdJMdjd GdeGdj dCfTWJgG(B.s
(3eQGLY U(B.409s
Keywords: (3GdQbGHI GdeGdjIs